LEXIC AND SEMANTIC FEATURES OF CONJUNCTIONS DIFFERENCES IN COMPARATIVE MEANING (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Abstract. This article discusses exploring the lexic and semantic features of conjunctions in linguistic studies respectively. The relevance of this study is working on lexic and semantic spheres of conjunctions and working on facing problems of this theme and to give proper solutions for the given challenges in linguistics. While carrying out the research it can be obvious that a reflective overview of the difficulties associated with the principle of differences in comparative meaning, the necessity and value of overcoming these challenges, and the promise of emerging research and technology in mitigating such issues.